Amorites and Canaanites - Kenyon, Kathleen M. (1966)
1963; I. The Intermediate Early Bronze-Middle Bronze Period in Palestine; II. The Intermediate Early Bronze-Middle Bronze Period in Syria; III. The Canaanites in Palestine and Syria; 30s.